An EWMA chart for sample range of Weibull data using weighted variance method - Atta, Abdu Mohammed Ali; Syed Yahaya, Sharipah Soaad; Zain, Zakiyah; Ali, Hazlina (2016)
This article proposes new EWMA chart in observing process standard deviation or dispersion with sample range of Weibull data using weighted variance method (WV).This control chart, called Weighted Variance EWMA sample range WV-EWMASR chart hereafter.The proposed WV-EWMASR chart compared with standard EWMASR of [7], skewness correction R chart (SC-R) suggested by[3]and Weighted Variance R chart (WV-R) proposed by [2], in the case of Type I and Type II errors when the data generated from Weibull distribution. Optimal parameters λ and k of the proposed WV-EWMASR and standard EWMASR are obtained via simulation using SAS program 9.4.The proposed WV-EWMASR control chart reduces to the standard EWMASR control chart of [7] when the process follow symmetric distribution. The proposed WV-EWMASR control chart has less Type I error than the standard EWMASR, SC-R and WV-R control charts, for Weibull distribution data. In case of Type II error, the proposed WV-EWMASR control chart is closer to EWMA chart with the exact limits than the standard EWMASR in [7].